Myopia management algorithm: annexe to the article titled Update and guidance on management of myopia: European Society of Ophthalmology in cooperation with International Myopia Institute - Tapasztó, Beáta; Flitcroft, Daniel Ian; Aclimandos, Wagih A.; Jonas, Jost B.; De Faber, Jan-Tjeerd H N; Nagy, Zoltán Zsolt; Kestelyn, Philippe G.; Januleviciene, Ingrida; Grzybowski, Andrzej; Vidinova, Christina Nicolaeva; Guggenheim, Jeremy A.; Polling, Jan Roelof; et al. (European journal of ophthalmology, 2023)
Myopia is becoming increasingly common in young generations all over the world, and it is predicted to become the most common cause of blindness and visual impairment in later life in the near future. Because myopia can cause serious complications and vision loss, it is critical to create and prescribe effective myopia treatment solutions that can help prevent or delay the onset and progression of myopia. The scientific understanding of myopia's causes, genetic background, environmental conditions, and various management techniques, including therapies to prevent or postpone its development and slow its progression, is rapidly expanding. However, some significant information gaps exist on this subject, making it difficult to develop an effective intervention plan. As with the creation of this present algorithm, a compromise is to work on best practices and reach consensus among a wide number of specialists. The quick rise in information regarding myopia management may be difficult for the busy eye care provider, but it necessitates a continuing need to evaluate new research and implement it into daily practice. To assist eye care providers in developing these strategies, an algorithm has been proposed that covers all aspects of myopia mitigation and management. The algorithm aims to provide practical assistance in choosing and developing an effective myopia management strategy tailored to the individual child. It incorporates the latest research findings and covers a wide range of modalities, from primary, secondary, and tertiary myopia prevention to interventions that reduce the progression of myopia.